Gram shbikas in outreach programme: a study of Mirjapur camp - Rahman, Dr. M. Mahbubur (© Research and Evaluation Division (RED), BRAC, 2016)
This study is conducted by Dr. M. Mahbubur Rahman, Research Sociologist, Bangladesh Rural Advancement Committee, Dhaka.